First-principles analysis on role of spinel (111) phase boundaries in Li4+3xTi5O12 Li-ion battery anodes. Issue 33 (8th August 2016) - Tanaka, Yoshinori; Ikeda, Minoru; Sumita, Masato; Ohno, Takahisa; Takada, Kazunori
Abstract : The practical anode material Li4+3 x Ti5 O12 is known to undergo a two-phase separation into Li7 Ti5 O12 and Li4 Ti5 O12 during charging/discharging. Abstract : The practical anode material Li4+3 x Ti5 O12 is known to undergo a two-phase separation into Li7 Ti5 O12 and Li4 Ti5 O12 during charging/discharging. This phase-separated Li4+3 x Ti5 O12 exhibits electron conduction, although individual phases are expected to be insulators. To elucidate the role played by spinel (111) phase boundaries on these physical properties, first principles calculations were carried out using the GGA+ U method. Two-phase Li7 Ti5 O12 /Li4 Ti5 O12 models are found to exhibit metallic characteristics near their phase boundaries. These boundaries provide conduction paths not only for electrons, but also for Li ions. Judging from the formation energy of Li vacancies/interstitials, the phase boundaries preferentially uptake or release Li via in-plane conduction and then continuously shift in a direction perpendicular to the phase boundary planes. The continuous phase boundary shift leads to a constant electrode potential. A three-dimensional network of cubic {111} planes may contribute to smooth electrochemical reactions.